Shipping and Logistics Management - Lun, Y. H. Venus; Lai, Kee-hung.; Cheng, T. C. Edwin; Yang, Dong. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book explains global trends and strategies in the shipping business, looking at the role of logistics service providers and at how information technology can help shipping operations. It also introduces best practices and advice that will allow professionals to improve the management of shipping and logistics activities. The book consists of sections examining shipping and trade, business strategies for shipping, intermodal container transport operations, and ports. This new edition adds a new fifth section with four new chapters that discusses contemporary issues in shipping. The new chapters are related to risk management in shipping, shipping security and safety, environmental and social sustainability, and a review of new technologies in the shipping industry and their future potential. An invaluable source of information for researchers and advanced, or graduate, students, Shipping and Logistics Management is also a useful reference for shipping practitioners and consultants.
Part I: Principles of shipping -- International trade and shipping -- Freight rate mechanism -- Bulk shipping market -- Container shipping market -- Part II: Shipping business -- Business strategy in shipping -- Growth of firms -- Fleet mix decision -- Liner shipping network -- Part III: Intermodal container transport -- Container transport chain -- Intermodal transport system -- Managing empty containers -- Container transport security -- Part IV: Port management -- Port operations -- Managing container terminals -- Agile port -- Port development -- Part V: Emerging issues in shipping -- Sustainability in shipping -- Shipping risk -- Security and safety -- Technological applications.
Keywords: Business logistics; Shipping; Industrial engineering; Production engineering; Production management; Industrial Management; Logistics; Maritime Economics; Industrial and Production Engineering; Operations Management; Industrial Management; Supply Chain Management